Construction of a tool to know the working conditions of the Peruvian artists - Yangali Vargas, Jorge Luis (2020)
This short paper is a preliminary to the research Project; That consists in studying the working conditions of Peruvian artists. Our objective in the article is present to academic community the construction of a survey guide that will allow them to delve into their employment problems. Methodologically, we continue the steps specified by the scientific methodology; This is the validation of the content through expert judgment and the application of a pilot test that determines a reliability value of α = 0.911 for the items formulated in this instrument. The survey guide combines open and closed questions in order to collect. The purpose of gathering, in addition to quantitative data, narratives of work experience.